Marine Heatwave of Sea Surface Temperature of the Oyashio Region in Summer in 2010–2016 - Miyama, Toru; Minobe, Shoshiro; Goto, Hanako (Frontiers in Marine Science, 2021)
The sea surface temperature (SST) of the Oyashio region in boreal summer abruptly increased in 2010 and high summertime SST repeated every year until 2016. Observations and an ocean reanalysis show that this marine heatwave occurred not only at the surface but also at deeper depths down to 200 m. Furthermore, salinity in summer also increased in parallel with the temperature. The rises in temperature and salinity indicate the strengthening of the Kuroshio water influence. The sea surface height and velocity show that the southward intrusion of the Oyashio near the coast in summer weakened from 2010 because of an increase in anticyclonic eddies from the Kuroshio Extension. The much more frequent existence of anticyclonic eddies to the east of the first intrusion of the Oyashio in summer is closely associated with the weakening of the first intrusion and the strengthening of the second intrusion. It is suggested that the rise in the water temperature could increase a catch of yellowtail (Seriola quinqueradiata) in northern Japan.